Mathematical Biology: Modeling the Dynamics of Ecosystems and Biodiversity - Khoironi Fanana Akbar; Daiki Nishida; Joni Wilson Sitopu (Yayasan Adra Karima Hubbi, 2024)
Background: Mathematical biology plays a crucial role in understanding the dynamics of ecosystems and biodiversity. By employing mathematical models, researchers can analyze complex biological interactions and predict changes within ecosystems over time. This approach is vital for addressing environmental challenges and informing conservation strategies. Objective: This study aims to develop mathematical models that accurately represent the dynamics of ecosystems and the factors influencing biodiversity. The focus is on identifying key interactions between species and their environment, as well as the implications of these interactions for ecosystem stability. Methodology: A combination of differential equations and computational simulations was employed to model various ecological scenarios. Data from field studies and ecological surveys were utilized to parameterize the models, allowing for realistic representations of species interactions and environmental influences. Results: Findings indicate that specific species interactions, such as predation and competition, significantly affect biodiversity and ecosystem dynamics. The models revealed thresholds beyond which ecosystems could shift to alternative stable states, emphasizing the importance of maintaining biodiversity for ecosystem resilience. Conclusion: This research highlights the value of mathematical modeling in the study of ecosystems and biodiversity. By providing insights into the intricate relationships between species and their environment, the study contributes to a better understanding of ecological dynamics and informs effective conservation strategies.